Engagement by Design: Exploring the Human Side of Digital Transformation Across Regions - Nursaid; Qomariah, Nurul (Indonesian Scientific Publication, 2025)
This study explores the human dimension of digital transformation by examining what drives and hinders employee engagement across regions. Using a mixed method approach, the research investigates psychological factors such as self-efficacy, conscientiousness, and technostress and the role of adaptive leadership and human-centered design. The findings reveal regional disparities in engagement, with South Asia showing the most positive outcomes due to supportive policies and cultural cohesion. Self-efficacy and conscientiousness strengthen engagement, while technostress remains a major barrier. Adaptive leadership proves critical in sustaining engagement during organizational change, and human-centered frameworks such as the HOPE model enhance both well-being and efficiency. Overall, the study concludes that sustainable digital transformation requires an integrated approach that blends psychology, leadership, inclusive design, and alignment with local policies.